Influence of Words of Mouth towards Product Satisfaction: A Qualitative Study on Takaful Customers in Pakistan - Dr. Muhammad Nawaz Iqbal; Muhammad Danish Ahsan; Dr Tooba Atif (Dialogue Social Science Review (DSSR), 2025)
Life insurance product satisfaction is quite challenging in Pakistan. Customers rarely seem satisfied with the life insurance product offer by insurer. Takaful is the successful channel in Pakistan to achieve customer market but the only tool is the word of mouth which keep the customer satisfied to avail the product. This research will explore the factors influence the product satisfaction of Takaful customer through word of mouth. The rationale of this research is to drive implications for the Takaful system during product pitch and customer services and increase volume of Takaful customers. This study was conducted using a qualitative methodology. Semi-structured interview transcripts have been used as a tool for research using thematic analysis. The findings, which take the shape of a theme made up of the factors that were explored are Word of mouth can have an impact on a Takaful customer to purchase a specific product, Trust is the strategic variable for Takaful distributors to achieve customer market, To ensure that all operations are conducted in accordance with sharia law, trust is crucial, Word of mouth develop customer satisfaction towards product with the element of religiosity. Trust is the strategy that Takaful company should create a plan or make an effort to train their agent or Takaful company representatives on providing effective administrative and communication services to their potential and current Family Takaful customers to ensure that all the Family Takaful participants receive the correct information on their contracts.